Ett nytt verktyg, samma plikter - En analys av generativ AI i advokatverksamhet i ljuset av god advokatsed - Eriksson,Amanda Madeleine Claire (2025)
Pursuant to Chapter 8, Section 4 of the Swedish Code of Judicial Procedure, Swedish lawyers (members of the Swedish Bar) must perform entrusted assignments conscientiously and with integrity and comply with good professional conduct. This requirement reflects the special responsibilities of the legal profession and, inter alia, engages the duty of confidentiality and the duty of discretion, the duty of professional competence and the duty of loyalty. This thesis examines how these duties are affected when generative artificial intelligence (GenAI) is used as a work tool in legal practice. The thesis has two aims. First, it identifies the ethical problems that may arise when GenAI is used in legal services, with particular focus on duty of confidentiality and the duty of discretion, the duties of care and professional competence, the duty of loyalty and conflicts of interest, and the requirement of independence. Second, it assesses the extent to which the current ethical framework is sufficient to address these problems and whether clearer guidance or further normative development is required. The analysis shows that GenAI primarily creates risks relating to the control of client information and access, especially where data may be stored, reused, or accessed by third parties within vendor chains. GenAI also raises quality and reliability concerns, as such systems may produce convincing but incorrect or fabricated content, increasing the need for verification before outputs are used in legal advice or procedural documents. In addition, the thesis high-lights loyalty and conflict-of-interest issues, particularly where the separation of client matters may be undermined by opaque information flows. Finally, the risk of over-reliance on GenAI may weaken independent professional judgment and accountability. The thesis concludes that GenAI is not inherently incompatible with good professional conduct. However, ethical compliance is conditional. To uphold professional duties, GenAI must be used under controlled conditions, client information must remain under the lawyer’s control, AI-generated output must be treated as preliminary material subject to systematic review and the final legal assessment and responsibility must remain with the lawyer. Overall, the existing ethical framework is largely sufficient at the level of principles, but further clarification at the level of application is needed to ensure predictability in GenAI use.
Keywords: AI; Generativ AI; Advokatetik; God advokatsed; Procedure; Processrätt